Respiratory Syncytial Virus (RSV) Neutralizing Antibodies at Birth Predict Protection from RSV Illness in Infants in the First 3 Months of Life. (28th May 2020) - Buchwald, Andrea G; Graham, Barney S; Traore, Awa; Haidara, Fadima Cheick; Chen, Man; Morabito, Kaitlyn; Lin, Bob C; Sow, Samba O; Levine, Myron M; Pasetti, Marcela F; Tapia, Milagritos D
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of viral pneumonia and bronchiolitis during the first 6 months of life. Placentally transferred antibodies can prevent severe RSV illness, and maternal immunization may reduce illness in young infants. Identification of protective antibody levels facilitates the advancement of vaccine candidates and maternal immunization. Methods: We conducted a nested case-control study with 587 Malian mother–infant pairs, followed from birth to age 6 months. RSV cases were infants who developed influenza-like illness (ILI) or pneumonia and were RSV-positive by polymerase chain reaction. Cases were matched to healthy controls and RSV-negative ILI controls. RSV-A and RSV-B neutralizing antibodies were measured in maternal, cord blood, and infant sera at age 3 and 6 months. Results: Maternal antibodies were efficiently transferred to infants. Maternal and infant RSV titers were strongly correlated. Infant antibody titers against RSV-A were 3 times higher than those against RSV-B. At birth, infants who remained healthy had significantly higher RSV-A and RSV-B titers compared with infants who subsequently contracted RSV. RSV-A inhibitory concentration (IC)80 titer >239 or RSV-B titer >60 at birth was significantly associated with being a healthy control compared with an RSV case within the first 3 months of life. RSV-A IC80 titers in cord blood were associated with decreased episodes of pneumonia. Conclusions: Maternally acquired RSV antibodies were associated with protection of infants against community-detected cases of RSV-ILI and pneumonia. RSV titers in cord blood can predict whether an infant will be infected with RSV or remain uninfected. Abstract : Maternally acquired respiratory syncytial virus (RSV) neutralizing antibodies were associated with infant protection against RSV up to 3 months. These findings indicate that RSV titers at birth can predict whether an infant will be infected with RSV or remain uninfected in early life.